Sortilin in Glucose Homeostasis: From Accessory Protein to Key Player? - Blondeau, Nicolas; Béraud-Dufour, Sophie; Lebrun, Patricia; Hivelin, Céline; Coppola, Thierry (Frontiers in Pharmacology, 2019)
The pharmacological properties and physiological roles of the type I receptor sortilin, also called neurotensin receptor-3, are various and complex. Sortilin is involved in important biological functions from neurotensin and pro-Nerve Growth Factor signaling in the central nervous system to regulation of glucose and lipid homeostasis in the periphery. The peripheral functions of sortilin being less extensively addressed, the focus of the current review is to discuss recent works describing sortilin-induced molecular mechanisms regulating blood glucose homeostasis and insulin signaling. Thus, an overview of several roles ascribed to sortilin in diabetes and other metabolic diseases are presented. Investigations on crucial cellular pathways involved in the protective effect of sortilin receptor on beta cells, including recent discoveries about regulation of cell fate, are also detailed. We also provide a special focus on insulin secretion regulation involving complexes between sortilin and neurotensin receptors. The last section will comment on the future research areas which should be developed to address the function of new effectors of the sortilin system in the endocrine apparatus.